Chemical Analysis of Urinary Stones - Sigdel, Ghanshyam; Lamichhane, Nirmal; K.C., Sudeep Raj; Belokar, W.K. (Journal of Society of Surgeons of Nepal, 2016)
Introduction: Urinary stone disease is a common urological problem. Chemical analysis of the urinary stones is a part of metabolic evaluation of first time or recurrent stone formers. The report of chemical analysis of stones may obviate the need for complete metabolic evaluation or can direct metabolic evaluation. In this study we aim to find out the chemical compositions of urinary stones in our population, so that the result might serve as a baseline for the related research in future. Methods: A prospective study was carried out in our institute with the qualitative chemical analysis of urinary stones. All patients operated for different urinary stones by various methods were included in the study. Statistical analysis was done by using Statistical Package for the Social Sciences Software (SPSS) Program for windows ® version 18. Results: A total of 55 patients were included in the study. Male to female ratio was 1.75. Mean age was 41.45 years. Ureteric and renal stones were most common accounting to 49 and 31 percentage respectively. All stones contained calcium. Calcium, phosphate, oxalate and uric acid were the major constituents of the stones representing 100, 94.5, 85.5 and 80 percentage of the stone specimen. Other constituents were amino acids, carbonate, magnesium and cystine. Conclusions: Urinary stones are of mixed chemical compositions. Further large scale prospective studies along with other parameters of metabolic work up are recommended to know more about the chemical compositions of urinary stones and its utility in clinical practice.